Holocene reef accretion of the inshore Kimberley Bioregion and response to sea-level changes - Solihuddin, Tubagus (Curtin University, 2016)
The Kimberley Bioregion of Northwest Australia is one of the world’s last great pristine marine environments and is broadly recognised as a “biodiversity hostspot” but is poorly known and studied. This project completed a comprehensive description of reef geomorphology and associated habitats, stratigraphy, palaeoecology, geochronology, accretion history along with shallow seismic profile. A combination of the data collected and interpreted provides the foundation for a scientifically based management plan of the Bioregion.